Child labour in historical perspective 1800-1985 : case studies from Europe, Japan and Colombia - Cunningham, Hugh; Viazzo, Pier Paolo (Florence : UNICEF, 1996)
BMLIK
Engels
Monografie
Keywords: kinderarbeid